Prognostic impact of complications after resection of early stage hepatocellular carcinoma. Issue 7 (15th February 2017) - Margonis, Georgios Antonios; Sasaki, Kazunari; Andreatos, Nikolaos; Nishioka, Yujiro; Sugawara, Toshitaka; Amini, Neda; Buettner, Stefan; Hashimoto, Masaji; Shindoh, Junichi; Pawlik, Timothy M.
Abstract : BACKGROUND: Resection is the most effective treatment for HCC. However, postoperative morbidity is common and its impact on long‐term oncological outcome remains unclear. METHODS: Long‐term outcomes of 774 patients who underwent curative resection for early stage HCC at Johns Hopkins Hospital and Toranomon Hospital were investigated after stratifying by the development of postoperative overall and infectious complications. RESULTS: A minor or major postoperative complication developed in 281 and 65 patients, respectively, while postoperative mortality was 1.3% ( n = 10). The 5‐year cumulative recurrence and overall survival(OS) rates were 57.2% and 76.4%, respectively. Overall postoperative complications independently predicted worse OS in multivariable analysis (HR = 1.42, P = 0.021). Complication severity did not correlate with OS ( P > 0.05). While infectious complications were not independent predictors of OS, the combination of blood transfusion and infectious complications led to significantly worse OS (66.3% vs. 44.9%, P = 0.008). Postoperative complications also correlated with increased recurrence risk, but only in patients with non‐cirrhotic parenchyma (55.0% vs. 47.7%, P = 0.035) or non‐viral hepatitis (55.6% vs. 44.4%, P = 0.002). CONCLUSIONS: Post‐operative morbidity independently predicted poor OS following hepatectomy for early stage HCC. A similar effect on recurrence was noted only in patients with favorable etiopathologic factors. Finally, the combination of peri‐operative transfusion and subsequent infectious complications was associated with a synergistic negative effect on prognosis.